Review article : Bacterial vaginosis in women - Mohammed Atiyah, Mostafa (International Journal of Psychosocial Rehabilitation, 2020)
Bacterial vaginosis is caused by the overgrowth of some bacteria naturally present in the vagina, Vaginal infection is most common in women, especially in pregnant women. The cause of this disorder is not known, nor is it caused by poor hygiene. women with vaginal bacteria Might not appear any signs or symptoms. Frequent washing and the use of scented soaps cause vaginal imbalance. The most common clinical symptoms of bacterial vaginosis include a thin homogeneous vaginal discharge, pH 4.5, the appearance of clue cells, and an amine odor after 10 percent of Potassium hydroxide. None of them no Lactobacilli in the vaginal fluid are normally detected by microscopy, Several ways of diagnosing BV, Clinical Quality Requirements, Gram Stain, Vaginal Cultures, Papanicolaou smears, Oligonucleotide probes, Gas-Liquid Chromatography, Proline Aminopeptidase Assay, Molecular Methods. This review focuses on the epidemiology, etiology, diagnosis, complications, and treatment of BV, with emphasis on the role of antimicrobial treatment options.